Distributed Computing in Sensor Systems 5th IEEE International Conference, DCOSS 2009, Marina del Rey, CA, USA, June 8-10, 2009, Proceedings - Krishnamachari, Bhaskar; Suri, Subhash; Heinzelman, Wendi; Mitra, Urbashi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2009)
The book constitutes the refereed proceedings of the Fifth International Conference on Distributed Computing in Sensor Systems, DCOSS 2009, held in Marina del Rey, CA, USA, in June 2009. The 26 revised full papers presented were carefully reviewed and selected from 116 submissions. The research contributions in this proceedings span many aspects of sensor systems, including energy efficient mechanisms, tracking and surveillance, activity recognition, simulation, query optimization, network coding, localization, application development, data and code dissemination.
Speed Dating Despite Jammers -- Fast Self-stabilization for Gradients -- Detection and Localization Sensor Assignment with Exact and Fuzzy Locations -- Minimum Variance Energy Allocation for a Solar-Powered Sensor System -- Optimal Rate Allocation of Compressed Data Streams in Multihop Sensor Networks -- Mote-Based Online Anomaly Detection Using Echo State Networks -- Adaptive In-Network Processing for Bandwidth and Energy Constrained Mission-Oriented Multi-hop Wireless Networks -- LazySync: A New Synchronization Scheme for Distributed Simulation of Sensor Networks -- Similarity Based Optimization for Multiple Query Processing in Wireless Sensor Networks -- Finding Symbolic Bug Patterns in Sensor Networks -- Distributed Continuous Action Recognition Using a Hidden Markov Model in Body Sensor Networks -- Online Coding for Reliable Data Transfer in Lossy Wireless Sensor Networks -- Compressed RF Tomography for Wireless Sensor Networks: Centralized and Decentralized Approaches -- Energy Adaptive Sensor Scheduling for Noisy Sensor Measurements -- Route in Mobile WSN and Get Self-deployment for Free -- A Sensor Network System for Measuring Traffic in Short-Term Construction Work Zones -- Empirical Evaluation of Wireless Underground-to-Underground Communication in Wireless Underground Sensor Networks -- Cheap or Flexible Sensor Coverage -- MCP: An Energy-Efficient Code Distribution Protocol for Multi-Application WSNs -- Optimal Allocation of Time-Resources for Multihypothesis Activity-Level Detection -- Distributed Computation of Likelihood Maps for Target Tracking -- Efficient Sensor Placement for Surveillance Problems -- Local Construction of Spanners in the 3-D Space -- Combining Positioning and Communication Using UWB Transceivers -- Distributed Generation of a Family of Connected Dominating Sets in Wireless Sensor Networks -- Performance of Bulk Data Dissemination in Wireless Sensor Networks.
Keywords: 9; Telecommunication; Computers, Special purpose; Electronic digital computers -- Evaluation; Algorithms; Computer engineering; Computer Communication Networks; Communications Engineering, Networks; Special Purpose and Application-Based Systems; System Performance and Evaluation; Algorithms; Computer Engineering and Networks